Evaluating digital literacy and media awareness: Impacts on middle school students’ digital security knowledge in Indonesia - Hidayat, Hendra; Alfaiz, Alfaiz; Ardi, Zadrian; Hidayah, Nur; Izzati, Umi Anugerah; Firman, Firman; Afdal, Afdal; Tririzky, Reza; Thanakodi, Suresh (LPMPP Universitas Negeri Yogyakarta, 2026)
In an increasingly complex technological landscape, digital literacy is essential for adolescents to navigate digital risks and advancements effectively. This quantitative study investigates the impact of digital literacy and media awareness on middle school students’ understanding of digital security and technological issues in Indonesia. Using a cross-sectional survey of 902 participants, data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital literacy has a significant positive effect on students’ media use, digital security management, and awareness of technological developments. Furthermore, Importance-Performance Map Analysis (IPMA) reveals that digital literacy is the most influential factor among the variables studied. The findings emphasize the importance of integrating digital literacy education into school curricula to foster responsible and secure digital behavior among students.